The Influence Of Competitive Strategy, Service Expectation, And Service Quality On Competitive Advantage Mediated By Customer Satisfaction at Pt Asuransi Tugu Pratama Indonesia Tbk - Febrizal Febrizal; Agustinus Miranda W; Widarto Rachbini (International Journal Labs, 2025)
This study aims to determine the Influence of Competitive Strategy, Service Expectation and Service Quality on Competitive Advantage Mediated by Customer Satisfaction. The sample used was all customers of PT Asuransi Tugu Pratama Indonesia Tbk amounting to 240 respondents. The research method used in this study is a mixed method or quantitative method and qualitative method. The technique used is proportional sampling with the help of the SEM (Structural Equation Modeling) program application operated through SmartPLS 3.0 Software. The results of this study indicate that: 1) Competitive Strategy has a positive and significant effect on Competitive Advantage. Innovation that is difficult for competitors to imitate is a key element in strengthening the company's position in the insurance market. 2) Service Expectation has a positive and significant effect on Competitive Advantage. Meeting customer service expectations has been shown to increase the company's competitiveness. 3) Service Quality has a positive and significant effect on Competitive Advantage. Customer trust in employee competence plays an important role in creating competitive advantage. 4) Customer Satisfaction has a positive and significant effect on Competitive Advantage and mediates the relationship between Competitive Strategy, Service Expectation, and Service Quality on Competitive Advantage. 5) Competitive Strategy has a positive and significant effect on Customer Satisfaction. Innovation and personalization-based strategies have been shown to increase customer satisfaction. 6) Service Expectation and Service Quality have a positive and significant effect on Customer Satisfaction. Consistent and customer-expected service is a major factor in building customer satisfaction. 7) Customer Satisfaction mediates the relationship between Competitive Strategy, Service Expectation, and Service Quality on Competitive Advantage, emphasizing the importance of focusing on customer experience. 8) Based on the SWOT and EFAS/IFAS analysis, the company's strategy that emphasizes innovation, technology-based services, and product uniqueness has succeeded in taking advantage of market opportunities while overcoming weaknesses, ensuring sustainable competitiveness.